Schistosoma mansoni Infection-Induced Transcriptional Changes in Hepatic Macrophage Metabolism Correlate With an Athero-Protective Phenotype - Cortes-Selva, Diana; Elvington, Andrew F.; Ready, Andrew; Rajwa, Bartek; Pearce, Edward J.; Randolph, Gwendalyn J.; Fairfax, Keke C. (Frontiers in Immunology, 2018)
Hepatic macrophages play an essential role in the granulomatous response to infection with the parasitic helminth Schistosoma mansoni, but the transcriptional changes that underlie this effect are poorly understood. To explore this, we sorted the two previously recognized hepatic macrophage populations (perivascular and Kupffer cells) from naïve and S. mansoni-infected mice and performed microarray analysis as part of the Immunological Genome Project. The two hepatic macrophage populations exhibited remarkably different genomic profiles. However, this diversity was substantially reduced following infection with S. mansoni, and in fact, both populations demonstrated increases in transcripts of the monocyte lineage, suggesting that both populations may be replenished by monocytes following infection. Pathway analysis showed a profound alteration in global metabolic pathways, including changes to phospholipid and cholesterol metabolism, as well as amino acid biosynthesis and glucagon signaling. These changes suggest a possible mechanism for the previously reported athero-protective effects of S. mansoni infection. Indeed, we find that male ApoE null mice fed a high-fat diet in combination with S. mansoni infection have reduced plaque area and increased glucose tolerance as compared to control mice. Transcript analysis of infected and control high-fat diet fed ApoE-/- mice confirm that ApoC1, Psat1, and Gys1 are all altered by infection, suggesting that altered hepatic macrophage metabolism is associated with S. mansoni- induced protection from hyperlipidemia, atherosclerosis, and glucose intolerance. These results suggest a previously unknown and unreported role of hepatic macrophages in the modulation of whole body lipid and glucose metabolism during infection and provide a template for examining the role of immunomodulation on the long-term metabolism of the host.